1984
DOI: 10.1111/j.1365-2125.1984.tb02363.x
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in prednisolone disposition as a result of time of administration, gender and dose.

Abstract: 1 The disposition of total and free prednisolone has been studied in four male and four female volunteers, each of whom received an intravenous dose of 0.075 mg/kg (low) and 1.5 mg/kg (high) of prednisolone at both 06.00 h and 18.00 h. 2 For the low dose, free prednisolone clearance was 14% lower (P = 0.012) and time-averaged prednisolone free fraction was 22% higher (P < 0.001) in the morning, there being no circadian difference in total prednisolone clearance. There was no circadian differences in prednisolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
39
0
1

Year Published

1991
1991
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 28 publications
2
39
0
1
Order By: Relevance
“…The remaining blood was centrifuged and the plasma harvested and frozen at −20° C until assayed. In addition, 4 ml blood was drawn into EDTA tubes at 0, 2,4,8,12,16,20, and 24 hours for the determination of helper T lymphocyte counts.During the methylprednisolone phase, each subject received an intravenous bolus dose of methylprednisolone sodium succinate (Solu-Medrol; The Upjohn Company, Kalamazoo, Mich.) into the arm contralateral to the one used for blood sampling. A dose of 0.6 mg/kg ideal body weight (IBW) methylprednisolone was used to provide a similar initial blood concentration of methylprednisolone in each subject (as attained in a typical 70 kg man after a 40 mg dose) and to ensure a detectable suppressive response.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The remaining blood was centrifuged and the plasma harvested and frozen at −20° C until assayed. In addition, 4 ml blood was drawn into EDTA tubes at 0, 2,4,8,12,16,20, and 24 hours for the determination of helper T lymphocyte counts.During the methylprednisolone phase, each subject received an intravenous bolus dose of methylprednisolone sodium succinate (Solu-Medrol; The Upjohn Company, Kalamazoo, Mich.) into the arm contralateral to the one used for blood sampling. A dose of 0.6 mg/kg ideal body weight (IBW) methylprednisolone was used to provide a similar initial blood concentration of methylprednisolone in each subject (as attained in a typical 70 kg man after a 40 mg dose) and to ensure a detectable suppressive response.…”
mentioning
confidence: 99%
“…As early as 1958, a gender-related difference in hepatic metabolism of corticosteroids had been noted in rats by Yates et al 10 In humans, two studies have found a 23% and 21% greater clearance of free prednisolone in female compared with male adult subjects. 11,12 Gender-related differences may also influence the pharmacodynamics of drugs, but this has not been studied extensively. An in vitro study evaluating whole blood platelet aggregation revealed that the antithrombotic effect of aspirin was significantly greater in men, most likely because of the difference in testosterone levels.…”
mentioning
confidence: 99%
“…Both theophylline and free prednisolone, which are metabolized by the mixed function oxidase system, were found to exhibit lower CL values after morning administration than after afternoon administration, with CL values differing by 14% to 22%. 8,9,28 No such differences were found in the metabolic CL of acetaminophen, but this drug is primarily cleared by way of conjugation as opposed to oxidation. 29 In our study, the mean CL of methylprednisolone, which is eliminated by the mixed function oxidase system, was lower in the morning than in the afternoon, resulting in a larger AUC after the 8 AM dose.…”
Section: Discussionmentioning
confidence: 99%
“…The second study 8 found circadian differences in the clearance (CL) of free prednisolone and the free fraction when it was given as a low dose. The third study 9 found circadian variation in all parameters investigated. To date, no human chronopharmacokinetic study with methylprednisolone has been reported.…”
mentioning
confidence: 85%
“…Approximately 2%-5% is excreted in the urine as prednisone. [44] The clearance of prednisolone is dose-dependent, [31][32][33], [44], [59], [60,64] due to the concentration-dependent protein binding, that is, at high doses the increased free fraction of prednisolone is reflected in a greater plasma clearance and apparent volume of distribution. The total body clearance of prednisolone has been reported to be 111 mL/min/1.73 m2 for a 5 mg dose and 194 mL/min/1.73 m2 for a 40 mg dose of prednisolone.…”
Section: Metabolism and Excretionmentioning
confidence: 99%